Tratamento da mordida cruzada posterior funcional em crianças: análise dos resultados obtidos com o expansor fixo Hyrax modificado - Lopes, Juliana Maria de Araújo [UNESP] (2015)
The project goal is to enable students to make the diagnosis of malocclusions in children , develop and implement treatment plans specifically in relation to the functional posterior crossbite during the stages of deciduous and mixed dentition through a treatment protocol with use of a fixed expander called " modified Hyrax ", and thus eliminate functional deviations of the jaw and reestablish the normal dentition development. The results have shown the improvement of oral health of the population assisted.